Investigating the formation and remodelling of myelinated axons in vivo - Williamson, Jill M. (The University of Edinburgh, 2020)
Myelin is a crucial component of the vertebrate nervous system, both in facilitating rapid conduction of action potentials and in metabolically supporting axons. Recent research has theorised that myelin sheaths play a more intricate role in nervous system function by regulating circuits in response to experience. The number, length, thickness, and distribution of myelin sheaths along an axon all influence its underlying conduction properties. Thus, establishing or changing particular myelin patterns along axons could refine the precise timing of signals to change circuit outputs. Yet, how the myelin patterns along single axons are established, how myelin is remodelled over time, and how neuronal activity affects these processes, is not yet fully understood. I sought to investigate how myelin is formed, remodelled and maintained over time along individual axons in the larval zebrafish central nervous system. I first characterised the formation of myelin patterns along two different subtypes of axon in the larval zebrafish spinal cord. Using transgenic tools and confocal microscopy, I performed live imaging of single axons over a period of time during developmental myelination. Reticulospinal (RS) axons are involved in locomotor circuits, and are myelinated in a synaptic vesicle release-dependent manner; whereas, Commissural Primary Ascending (CoPA) axons are involved in sensory processing circuits, and are myelinated in a synaptic vesicle release-independent manner. I hypothesised that myelin patterns along axons are formed in a circuit-dependent fashion, and, therefore, that axons from different circuits would exhibit different myelin patterns. However, I found that both RS and CoPA axons have very similar myelin patterns, in terms of their myelin sheath number, length, myelin coverage, and nodal gap length, and that these patterns are established within a defined time window after the onset of myelination. I, then, assessed how myelin sheaths are remodelled along RS and CoPA axons over time, and found that myelin sheaths could either grow or shrink in length, or could be fully retracted from the axon itself. I hypothesised that myelin remodelling would occur along axons which use activity-related signals to regulate their myelination, and therefore, that RS axons would exhibit more myelin remodelling than CoPA axons. However, I found that RS and CoPA axons exhibited very similar degrees of myelin remodelling. Finally, I used a chemogenetic tool and live imaging by confocal microscopy to investigate how increasing activity in individual RS axons affects the dynamics of myelin sheath growth and the formation of myelin patterns. I found that increasing neuronal activity promotes the early growth of myelin sheaths within a critical period; after this period, neuronal activity no longer affects myelin sheath dynamics along RS axons. By promoting this early sheath growth, activity can change the myelin pattern established along individual RS axons. Collectively, this research begins to elucidate how individual myelinated axons are formed and maintained during nervous system development, and the cellular mechanisms by which neuronal activity may regulate this process.
Keywords: myelin; myelin sheaths; zebrafish; zebrafish spinal cord; myelinated axons; live imaging; axons; myelin sheath development; CoPA; CoPA axons; RS axons